2001
DOI: 10.1053/bbmt.2001.v7.pm11760148
|View full text |Cite
|
Sign up to set email alerts
|

Successful allogeneic stem cell transplantation with nonmyeloablative conditioning in patients with relapsed hematologic malignancy following autologous stem cell transplantation

Abstract: The use of myeloablative preparative therapy and allogeneic stem cell transplantation (alloSCT) as salvage therapy for adult patients with relapsed hematologic malignancy after autologous stem cell transplantation (autoSCT) is generally unsuccessful due to very high treatment-related mortality rates. We evaluated the outcome of HLA-matched related donor alloSCT following nonmyeloablative preparative therapy in 13 patients (median age, 38 years) with relapsed hematologic malignancies (Hodgkin's disease, n = 4; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…In the setting of disease progression after ASCT, nonmyeloablative allogeneic transplantation appears to have lower rates of transplant-related mortality compared to conventional transplantation, with long-term diseasefree survival rates reported to be between 20 and 35%. [42][43][44] These encouraging results warrant prospective studies of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of disease progression after ASCT, nonmyeloablative allogeneic transplantation appears to have lower rates of transplant-related mortality compared to conventional transplantation, with long-term diseasefree survival rates reported to be between 20 and 35%. [42][43][44] These encouraging results warrant prospective studies of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] The rationale behind this strategy is to decrease the high TRM observed after myeloablative allo-SCT, though preserving the GVT effect. In addition, RIC allo-SCT allows patients with significant coexistent medical problems to undergo allo-SCT.…”
Section: Non-myeloablative or Ric Allo-hsctmentioning
confidence: 99%
“…One out of six patients (17%) experienced grade X2 acute GVHD only after abrupt cyclosporin discontinuation and a interferon therapy for life-threatening tumor progression. T-cell chimerism was 23% (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) on day 28, 32% (10-35) on day 100, 78% (49-95) on day 180 and 99.5% (99-100) on day 365. Three out of four patients who had measurable disease before the transplant experienced a complete response.…”
Section: Discussionmentioning
confidence: 99%
“…DLI given early (around day 40) after a T-cell depleted NMSCT have been previously reported to convert mixed into complete donor chimerism. 23,24 Thus, we hypothesized that CD8-depleted pre-emptive DLI given in our patients on days 40 and 80 after the transplant were critical to avoid transplant rejection. Similarly, it has been shown that extending the duration of CyA from 35 to 100 days after the transplant favorably influenced stable donor engraftment in dogs conditioned with 100 cGy TBI and post grafting immunosuppression combining CyA and MMF.…”
Section: Discussionmentioning
confidence: 99%